EFFECT OF DIETARY SUPPLEMENTATION WITH DIFFERING LEVELS OF PROPOLIS ON PRODUCTIVITY AND BLOOD PARAMETERS IN BROILER CHICKS - Rabia J. Abbas (Basrah Journal of Veterinary Research)
The experiment was conducted to study the effect of adding propolis powder to the diet on productive , carcass characteristics and blood parameters in broiler chicks. Total of 180 1- day- old chicks were distributed randomly among four dietary treatments of propolis 0 , 0.5 , 1.5 and 2.5 g/kg diets . Each treatment was contain three replicate (15 birds / pen ). The results revealed that propolis supplementation at levels of 0.5 and 1.5 g/kg significantly (p